On the issue of bankruptcy of a peasant (farm) economy - Morozova Oksana; Kichalyuk Olga (E3S Web of Conferences, 2021)
The article examines the issues of legal regulation of the bankruptcy of a peasant (farm) economy in Russia. The authors analyze the legislation that determines the legal basis for bankruptcy, especially the bankruptcy of a peasant (farm) economy, methods of state support for this entity as well as some shortcomings in the legal regulation of bankruptcy of peasant farms as one of the areas of the agro-industrial complex. The article notes the exceptional importance of special norms in regulating the activities of peasant farms and the need to codify legislation in this area due to its specificity.